Pernikahan Dini Penduduk di Pulau Tidung – Kepulauan Seribu. Laporan Awal Pengabdian kepada Masyarakat FK UKI - Abraham Simatupang; Yunita Sitompul; Robert Sirait (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
Although there are already restrictions on the age of marriage according to Law No. 16 of 2019 article 7 paragraph 1 which reads: Marriage is only allowed if the man and woman have reached the age of 19 (nineteen) years, early marriage is still a problem in Indonesia. Early marriage has quite a lot of impact not only on the marriage partner, but also on their descendants and families. The divorce rate is quite high and the health rate and family economy also have an effect. Based on this, in the FK UKI Community Service activities in June 2022, data collection has been carried out related to the early marriage history of residents of Tidung Island-Thousand Islands, Jakarta. There were 99 respondents who had a history of early marriage, with the youngest marriage age was 10 years old and the oldest was 18 years old. The last education they had graduated was elementary school (69.7%) with a job as “housewife". This shows that although the Marriage Law has been assigned since 1974 and amended in 2019, the problem of early marriage is still high, and this certainly affects the government's performance to achieve the achievements of the Sustainable Development Goals (SDGs). Therefore, it is necessary to conduct counseling and monitoring to parents, the younger generation and other community institutions, so that early marriage no longer occurs.